ANALYSIS OF WORK CLIMATE AND WORK ETHIC ON TEACHER PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE AT SMA NEGERI 1 PESAM IN BENER MERIAH REGENCY - Masfirah; Mesra B; Sri Rahayu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the influence of work climate and work ethic on teacher performance, with motivation as an intervening variable, at SMA Negeri 1  Pesam, Bener Meriah Regency. Using a quantitative approach, data was collected from 66 teachers and analyzed using SmartPLS. The results indicate that work climate and work ethic have a positive and significant effect on motivation, and motivation, in turn, positively and significantly affects teacher performance. Work climate also has a direct positive and significant impact on teacher performance. However, work ethic does not have a significant direct effect on teacher performance, and motivation does not mediate the relationship between work climate and teacher performance. The findings suggest that fostering a positive work climate and strengthening work ethic can enhance teacher motivation and ultimately improve teacher performance.